Fundamentos sociojurídicos en materia penal del adolescente infractor frente al fenómeno 1del reclutamiento forzado (2013)
This article analyzes the foundations established in criminal matters for youngoffenders and their sociological consequences, in the specific case of armed conflictin Colombia and its relationship with the phenomenon of forced recruitment, whichwould involve the development of prevention policies aimed at this special type ofvulnerable population given the characteristics of their environment.